The prevalence and distribution of sheep scab in Wales: a farmer questionnaire survey. Issue 2 (18th January 2018) - CHIVERS, C.‐A.; ROSE VINEER, H.; WALL, R.
Abstract: Outbreaks of ovine psoroptic mange in the U.K. have increased 100‐fold since its deregulation in 1992, with the highest prevalence in Wales, a region of high sheep density. A cross‐sectional, retrospective, questionnaire‐based survey of 7500 members of the association of Welsh lamb and beef farmers [Welsh Lamb and Beef Producers Ltd (WLBP)] was used to investigate the prevalence and distribution of sheep scab in this region in 2015. The survey was completed by 14.0% ( n  = 972) of potential respondents. Scab outbreaks were reported on 15.8% ( n  = 154) of farms in 2015. However, 29.0% ( n  = 282) of farms reported at least one scab outbreak and 2.4% ( n  = 23) of farms had experienced between six and 10 outbreaks in the previous 10 years. Most outbreaks occurred during September–January (83.0%, n  = 150), and were clustered around Brecon (mid‐Wales) and Bangor (North Wales). Farmers who used common grazing were significantly more likely to report scab outbreaks in the previous 10 years than farmers who did not. No quarantine procedures for sheep bought in were used by 29.0% ( n  = 262) of farmers. Future research should be directed towards the development of localized management programmes, with a particular focus on areas of common grazing. Abstract : The mite Psoroptes ovis (male pictured) is the causative agent of sheep scab. 16% of sheep farmers in Wales reported an outbreak of sheep scab in 2015. Regional foci of scab prevalence are evident in central and north Wales.